Characterization of the Nonendocrine Cell Populations in Human Embryonic Stem Cell–Derived (hESC) Islet-Like Clusters Posttransplantation. (October 2021) - Jensen, Nikolai K.; Ingvorsen, Camilla; Petersen, Dorthe R.; Pereira, Maria J.; Lu, Tess T. H.; Alsted, Thomas J.; Kirkegaard, Jeannette S.; Keane, Kevin A.
Islet-like clusters derived from human embryonic stem cells (hESC) hold the potential to cure type 1 diabetes mellitus. Differentiation protocols of islet-like clusters lead to the generation of minor fractions of nonendocrine cells, which are mainly from endodermal and mesodermal lineages, and the risk of implanting these is unclear. In the present study, the histogenesis and the tumorigenicity of nonendocrine cells were investigated in vivo. Immunodeficient mice were implanted under the kidney capsule with islet-like clusters which were derived from differentiation of cells batches with either an intermediate or poor cell purity and followed for 8 or 26 weeks. Using immunohistochemistry and other techniques, it was found that the intermediate differentiated cell implants had limited numbers of small duct-like cysts and nonpancreatic tissue resembling gastrointestinal and retinal pigmented epithelium. In contrast, highly proliferative cystic teratomas were found at a high incidence at the implant site after 8 weeks, only in the animals implanted with the poorly differentiated cells. These findings indicate that the risk for teratoma formation and the amount of nonpancreatic tissue can be minimized by careful in-process characterization of the cells and thus highlights the importance of high purity at transplantation and a thorough ex-vivo characterization during cell product development.